The Debate on Basco-Iberian Numerals: An Approach from Linguistic Typology (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
From a linguistic typology perspective, some clarifications are offered to the debateon possible Iberian numerals. First, to determine whether these forms can be considerednumerals, and second, whether their origin is due to borrowing or genetic relationship. For thefirst question, the proposal by Orduña and Ferrer i Jané is summarized, drawing on research onlinguistic universals and numerals, as well as on cognitive linguistic studies by Hurford. For thesecond question, The World Loanword Database is reviewed, focusing on instances ofborrowing in numeral systems. An in-depth analysis is conducted on three languages from thesample, and the circumstances in which the phenomenon occurs are extrapolated. The findingssuggest a higher probability of borrowing than previously expected, although under specificconditions.
Keywords: Numerals; Borrowing; Cardinality Principle; Typology; Universals